BUSINESS AND BUDDHIST ETHICS IN GLOBAL PERSPECTIVE - Sivasai, Chintala Venkata (ShodhKosh: Journal of Visual and Performing Arts, 2023)
A crucial component of the modern world is business. Economic considerations have a significant impact on people's daily life. Seeing human existence solely from an economic perspective may be seen to be unduly restrictive because it encompasses so many other aspects as well. Unfortunately, it seems that the majority of people in today's society are driven solely by their financial situation. The question of how faith will benefit the people in this circumstance is raised by this truth. By referring to Buddhist teachings, the author hopes to provide an answer to this question. The main points of the piece will be: "How to handle business while simultaneously having a positive future for people and society.